The right to the camp: Spatial politics of protracted encampment in the West Bank. (November 2017) - Woroniecka-Krzyzanowska, Dorota
Abstract: Most theoretical models of refugee camps draw on the work of Giorgio Agamben and regard them as sites of exception set outside the normal juridical order, designed to strip refugees of their citizenship and reduce them to bare life. Yet, the complex realities of protracted camps challenge the distinctions between camp and city, and exception and citizenship. To contend with this complexity, it is necessary to move away from essentialized models and address the material, social, and political realities of protracted camps. I draw on the concept of 'the right to the city' to engage in discussion about civil rights of camp communities within the physical and political spaces of their prolonged residence. Based on ethnographic fieldwork in a Palestinian refugee camp in the West Bank, I investigate (1) the articulations of exception that have shaped the means, conditions and character of its spatial development; and (2) bottom-up responses by which the residents address the reality of multifaceted neglect and political struggles around camp space. In particular, I focus on the camp leadership's efforts to claim their community's right to development, agency over the production and governance of camp space, and recognition of their political autonomy and camp character - a set of claims that can be called, 'the right to the camp'. Highlights: Protracted camps challenge the distinctions between camp and city, exception and citizenship. In protracted camps exception is a multifaceted construct produced by state and non-state actors. Spatial politics of exception shape the development of protracted camps. 'The right to the camp' approach is discussed based on the concept of 'the right to the city'. Underlying question: what civil rights should camp communities have to the spaces of their long-term residence?